A study of the challenge of sustainability - Ming , Wong Tai; Sorooshian, Shahryar (Journal of Management and Science, 2013)
This paper is to identify the challenge of sustainability of timber industry and rank the challenge of sustainability of the timber industry. With the result of the research, the timber industry owner can know which challenge is most critical and they can take some action on that challenge.